2018
DOI: 10.1038/nbt.4272
|View full text |Cite
|
Sign up to set email alerts
|

De novo domestication of wild tomato using genome editing

Abstract: Nature Research wishes to improve the reproducibility of the work that we publish. This form provides structure for consistency and transparency in reporting. For further information on Nature Research policies, see Authors & Referees and the Editorial Policy Checklist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
351
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 630 publications
(364 citation statements)
references
References 42 publications
3
351
0
10
Order By: Relevance
“…Further practical testing of the above approach would in addition reveal if there is merit in the ‘redomestication’ of major crops from their wild relatives and progenitors as a strategy for efficiently accessing wild gene pools for traits lost in the development of advanced cultivars but now considered beneficial for addressing agriculture's sustainability challenges (Langridge & Waugh, ). Recent research using CRISPR/Cas9 gene editing of target domestication‐related genes has shown promise for redomestications, with domesticated phenotypes that retain important wild attributes achievable starting from crop wild progenitors in the case of tomato (T. Li et al ., ; Zsögön et al ., ). It is known that wild relatives, progenitors and landraces of a number of major crops contain more variation in traits related to resource use efficiency and a plant's ability to interact positively with other crops and noncrop biotic components in complex production systems than do narrowly diverse advanced cultivars developed for monoculture (Kapulnik & Kushnir, ; Mutch & Young, ; Martín‐Robles et al ., ).…”
Section: Future Outlookmentioning
confidence: 97%
“…Further practical testing of the above approach would in addition reveal if there is merit in the ‘redomestication’ of major crops from their wild relatives and progenitors as a strategy for efficiently accessing wild gene pools for traits lost in the development of advanced cultivars but now considered beneficial for addressing agriculture's sustainability challenges (Langridge & Waugh, ). Recent research using CRISPR/Cas9 gene editing of target domestication‐related genes has shown promise for redomestications, with domesticated phenotypes that retain important wild attributes achievable starting from crop wild progenitors in the case of tomato (T. Li et al ., ; Zsögön et al ., ). It is known that wild relatives, progenitors and landraces of a number of major crops contain more variation in traits related to resource use efficiency and a plant's ability to interact positively with other crops and noncrop biotic components in complex production systems than do narrowly diverse advanced cultivars developed for monoculture (Kapulnik & Kushnir, ; Mutch & Young, ; Martín‐Robles et al ., ).…”
Section: Future Outlookmentioning
confidence: 97%
“…The genome editing of CLV3 orthologues can produce multilocular siliques in several dry fruit crops, including Brassica rapa and B. napus (Fan et al , ; Yang et al , ). In addition, the genome editing of CLV1/2/3 also produced multiple locular fruits with increased size in fleshy fruit crops, such as tomato and groundcherry (Lemmon et al , ; Li et al , ; Rodrı´guez‐Leal et al , ; Xu et al , ; Zsögön et al , ).…”
Section: Receptor Kinase Signallingmentioning
confidence: 99%
“…Such information is essential if a comprehensive genome editing approach is to be applied. Some initial targets for fruit size have been targeted using editing approaches, with some success (Lemmon et al , ; Li et al , ; Rodríguez‐Leal et al , ; Zsögön et al , ), suggesting that, with a more comprehensive understanding of the genetic and signalling pathways underlying this trait, major gains could be achieved. In addition to improving fruit size in elite germplasm, genome editing can be used for improvement of orphan crops (Lemmon et al , ) or de novo domestication of crop wild relatives (Zsögön et al , ), which often harbour agronomically valuable disease resistance traits (Dangl et al , ).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Very recently, Zsögön et al . () and Li et al . () engineered the S. pimpinellifolium wild ancestor of cultivated tomato by CRISPR multiplexing with six gRNAs, which resulted in the generation of gene‐edited plants with characteristics similar to those of cultivated tomato, i.e.…”
Section: From Trait Discovery To Trait Engineering: Gene Editingmentioning
confidence: 88%
“…Then, the ideal would be to reproduce directly in elite lines the allelic variation(s) responsible for improvement of the trait(s) of interest. Thanks to the recent advances in GE technologies, reaching this objective can be expected in the very near future, as very recently demonstrated by several studies (Rodríguez‐Leal et al ., ; Li et al ., ; Zsögön et al ., ).…”
Section: From Trait Discovery To Trait Engineering: Gene Editingmentioning
confidence: 97%